2015
DOI: 10.2174/1871520615666150716105057
|View full text |Cite
|
Sign up to set email alerts
|

How to Make a Non-Antigenic Protein (Auto) Antigenic: Molecular Complementarity Alters Antigen Processing and Activates Adaptive-Innate Immunity Synergy

Abstract: Evidence is reviewed that complementary proteins and peptides form complexes with increased antigenicity and/or autoimmunogenicity. Five case studies are highlighted: 1) diphtheria toxin-antitoxin (antibody), which induces immunity to the normally non-antigenic toxin, and autoimmune neuritis; 2) tryptophan peptide of myelin basic protein and muramyl dipeptide ("adjuvant peptide"), which form a complex that induces experimental allergic encephalomyelitis; 3) an insulin and glucagon complex that is far more anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 170 publications
0
21
0
Order By: Relevance
“…What, then could be the molecular mechanism for the sense-antisense complementarity at the protein/peptide level? Since sense and antisense peptides can interact with each other with increased probability, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] one can assume the presence of some binding specificity. This specificity was described as "amphipathic recognition" for a hydrophilic-hydrophobic mechanism of sense-antisense peptide binding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…What, then could be the molecular mechanism for the sense-antisense complementarity at the protein/peptide level? Since sense and antisense peptides can interact with each other with increased probability, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] one can assume the presence of some binding specificity. This specificity was described as "amphipathic recognition" for a hydrophilic-hydrophobic mechanism of sense-antisense peptide binding.…”
Section: Methodsmentioning
confidence: 99%
“…Curiously enough, what seems to be entirely nucleic acid-specific sense-antisense complementarity has found its way into the protein world too. In fact, multiple studies indicated that sense and antisense peptides can interact with each other with increased probability, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] with the length of known interacting sense-antisense peptides being varied between 4 and 19 amino acids. [17][18][19] Here, the amino acid sequence of a sense peptide is encoded by the nucleotide sequence (read 5 0 !…”
Section: Introductionmentioning
confidence: 99%
“…Additional examples of enhanced immunogenicity and autoimmunity associated with complementary antigen complexes are reviewed in [ 136 ]. These include a diphtheria toxin-antitoxin (antibody) complex that induces an autoimmune polyneuritis similar to Guillain-Barré syndrome [ 137 , 138 , 139 ], the induction anti-insulin antibodies in type 1 diabetes by an insulin-glucagon complex [ 140 ] and improved antigen presentation to macrophages and dendritic cells by heat shock protein-viral antigen complexes [ 141 ].…”
Section: Toll-like Receptor Activation In Autoimmune Diseasementioning
confidence: 99%
“…In sum, for a number of AD with well-defined animal models and/or molecular targets, including two AD featured here—AM and MS—evidence exists that initiating antigens exhibit complementarity towards each other by binding directly to each other and/or by inducing immune responses that have idiotype–anti-idiotype characteristics. Notably, antigen presenting cells are known to process such antigen complexes differently than are their individual antigenic components (reviewed in [ 136 ]). Antigenic complexes are more stable than their components to proteolytic and oxidative degradation and thus more likely to be perceived by the immune system as antigenic; they are digested into different fragments by the proteasome than are their individual components; and such complexes can be perceived by the immune system as distinctly novel antigens that differ significantly from their individual components [ 136 ].…”
Section: Toll-like Receptor Activation In Autoimmune Diseasementioning
confidence: 99%
“…It is well known that molecules to which the immune system is tolerant can be made antigenic through chemical or physical alteration and that non-antigens can be made antigenic by chemically coupling them to an antigen or hapten (e.g., Landsteiner and van der Scheer, 1936;Eisen, et al, 1952). The formation of complementary antigen complexes can have the same effects (reviewed in Root- Bernstein, 2015).…”
Section: Act Altered Antigen Processing and The Abrogation Of "Self-mentioning
confidence: 99%